2021
DOI: 10.1186/s13578-021-00656-8
|View full text |Cite
|
Sign up to set email alerts
|

Differing susceptibility of C57BL/6J and DBA/2J mice—parents of the murine BXD family, to severe acute respiratory syndrome coronavirus infection

Abstract: The ongoing coronavirus disease-2019 (COVID-19) pandemic, caused by a novel coronavirus termed severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that is closely related to SARS-CoV, poses a grave threat to global health and has devastated societies worldwide. One puzzling aspect of COVID-19 is the impressive variation in disease manifestations among infected individuals, from a majority who are asymptomatic or exhibit mild symptoms to a smaller, largely age-dependent fraction who develop life-threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…We found that K18‐hACE2 mice treated with S/GFP EV had markedly reduced morbidity (early body weight loss) after infection with a lethal dose of SARS‐CoV‐2 (Figure 6c ). The apparent transiency of the weight loss, or rebound in surviving control mice is consistent with reported data (Falach et al., 2021 ; Li et al., 2021 ; Sun et al., 2021 ) and may represent a selection of more resilient animals in the group. Importantly, the overall survival of mice treated with S/GFP EVs was significantly increased to 65% compared to 20% in control mice, which received only GFP‐containing EVs (Figure 6d ).…”
Section: Resultssupporting
confidence: 89%
“…We found that K18‐hACE2 mice treated with S/GFP EV had markedly reduced morbidity (early body weight loss) after infection with a lethal dose of SARS‐CoV‐2 (Figure 6c ). The apparent transiency of the weight loss, or rebound in surviving control mice is consistent with reported data (Falach et al., 2021 ; Li et al., 2021 ; Sun et al., 2021 ) and may represent a selection of more resilient animals in the group. Importantly, the overall survival of mice treated with S/GFP EVs was significantly increased to 65% compared to 20% in control mice, which received only GFP‐containing EVs (Figure 6d ).…”
Section: Resultssupporting
confidence: 89%
“…Thus careful studies are needed to verify the effectiveness and suitability of these strains as model organisms. Studies employing mouse-adapted SARS-CoV-2 strains have primarily been performed in BALB/c mice [ 6 , 8 , 9 , 13 , 14 ] and focused on a single sex or single age cohorts [ 3 , 10 , 12 , 15 , 16 ], or have employed highly adapted and virulent variants that limit the ability to comprehensively examine infection and recovery [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that there is a myriad of disease manifestation among SARS-CoV-2 infected patients 27 . The use of humanized mice with variations in immune responses can represent diverse cohorts of people.…”
mentioning
confidence: 99%